2017
DOI: 10.1007/s10147-017-1138-6
|View full text |Cite
|
Sign up to set email alerts
|

A phase II study of 5-fluorouracil/L-leucovorin/oxaliplatin (mFOLFOX6) in Japanese patients with metastatic or unresectable small bowel adenocarcinoma

Abstract: BackgroundSeveral studies have suggested that chemotherapy prolonged survival in patients with metastatic or recurrent small bowel adenocarcinoma (SBA); however, there is still no standard chemotherapy regimen. Here, we evaluated the efficacy and safety of a 5-fluorouracil (5-FU)/L-leucovorin (l-LV)/oxaliplatin (mFOLFOX6) protocol as a first-line therapy for patients with SBA.Patients and methodsThis was a multicenter, single-arm, open-label phase II study. Eligibility criteria included histologically confirme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
38
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 37 publications
4
38
0
Order By: Relevance
“…In 2015, a large‐scale retrospective study included 1982 CRC patients with unresectable metastasis revealed that, even palliative primary tumor resection significantly improved CSS among the whole patient population 20 . And for metastatic SBA, several research studies also found that resection of primary tumor is one of the independent factors of OS 19,21,22 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2015, a large‐scale retrospective study included 1982 CRC patients with unresectable metastasis revealed that, even palliative primary tumor resection significantly improved CSS among the whole patient population 20 . And for metastatic SBA, several research studies also found that resection of primary tumor is one of the independent factors of OS 19,21,22 …”
Section: Discussionmentioning
confidence: 99%
“…For stage IV or unresectable SBA patients, several analyses found that palliative chemotherapy could prolong survival compared with best supportive care or without treatment 5,18,19,24,26 . Among different chemotherapy regimens, combination chemotherapy including platinum and 5‐FU are primarily recommended as yet, with well tolerance and better OS 6,8‐11,21,22,25‐27 . As distinct genomic profiling of SBA was revealed compared with CRC and gastric carcinoma, 28 it seems unreasonable that the approach proposed for CRC or gastric carcinoma was completely adopted for the treatment of SBA.…”
Section: Discussionmentioning
confidence: 99%
“…119 Likewise, another phase II study reported an ORR of 45% for 24 patients with metastatic or unresectable SBA who were treated with FOLFOX, with a median progression-free survival (PFS) and OS of 5.9 and 17.3 months, respectively. 120 These response rates to CAPEOX and FOLFOX were much higher than the 18% response rate seen in another small phase II study that evaluated 5-FU/doxorubicin/mitomycin C in patients with metastatic SBA. 121 Adverse events reported across these 3 trials were similar, with neutropenia, thrombocytopenia, nausea, vomiting, diarrhea, peripheral neuropathy, and fatigue reported most frequently.…”
Section: Folfox or Capeox As First-line Therapymentioning
confidence: 75%
“…121 Adverse events reported across these 3 trials were similar, with neutropenia, thrombocytopenia, nausea, vomiting, diarrhea, peripheral neuropathy, and fatigue reported most frequently. [118][119][120] Retrospective studies have supported the results of these trials, reporting that the combination of a fluoropyrimidine with oxaliplatin was the most effective first-line therapy for advanced SBA. 111,122,123 Based on these data, FOLFOX or CAPEOX are recommended as first-line therapy options for treatment of patients with advanced SBA who are appropriate for intensive therapy.…”
Section: Folfox or Capeox As First-line Therapymentioning
confidence: 89%
“…As shown in Table 4, the best results were recorded with a combination of a fluoropyrimidine and oxaliplatin. With either FOLFOX [61,62] or capecitabine and oxaliplatin (CAPOX) [63], a response rate of 45-50%, a disease control rate of 80-90% and a median overall survival of 15-20 months were observed. The addition of irinotecan to the combination of a fluoropyrimidine and oxaliplatin has resulted in higher efficacy but also severe hematological toxicity in colorectal cancer studies [64][65][66].…”
Section: Systemic Metastasesmentioning
confidence: 99%